2013
DOI: 10.1055/s-0033-1339925
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Polymerizable Benzocyclobutene that Undergoes Ring-Opening Isomerization at Reduced Temperature

Abstract: 1-Ethoxyvinylbenzocyclobutene is a substituted benzocyclobutene that undergoes radical polymerization to produce polymers that can be crosslinked at 100-150°C. The 4-and 5-vinyl isomers are synthesized in a 1:4 ratio via a halogenated benzyne intermediate produced from anthranilic acid, followed by cycloaddition with ethyl vinyl ether and replacement of the halogen atom with a vinyl group.Key words: benzocyclobutene, cycloaddition, ring-opening isomerization, Kumada coupling, benzyne Bicyclo[4.2.0]octa-1,3,5-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Most significant are the results of compounds 6b and 6c, which have exothermic transitions at significantly reduced temperatures (176 and 148 °C, respectively). It should be noted that compound 6c performs similarly to the 1-ethoxy styrene synthesized by Pugh et al (135 °C as reported), 9 and thus lends credence to the hypothesis that the 1-alkoxy group is a key contributor to cross-linking temperature because the delta-trifluoromethyl groups appear to have no effect. The work by Harth et al did not utilize DSC data; therefore, a direct comparison of cross-linking temperature cannot be made.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most significant are the results of compounds 6b and 6c, which have exothermic transitions at significantly reduced temperatures (176 and 148 °C, respectively). It should be noted that compound 6c performs similarly to the 1-ethoxy styrene synthesized by Pugh et al (135 °C as reported), 9 and thus lends credence to the hypothesis that the 1-alkoxy group is a key contributor to cross-linking temperature because the delta-trifluoromethyl groups appear to have no effect. The work by Harth et al did not utilize DSC data; therefore, a direct comparison of cross-linking temperature cannot be made.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It has been reported that functionalization of the alkyl ring on BCB can significantly lower the temperature at which the electrocyclic ring opening reaction responsible for cross-linking takes place . Pugh et al described the synthesis of 1-ethoxy-4-vinylbenzocyclobutene, which cures at a significantly reduced temperature. The key step in their synthesis of substituted BCB involves use of an ortho -diazonium carboxylate salt as a benzyne precursor.…”
Section: Introductionmentioning
confidence: 99%
“…Due to insolubility of the nal cross-linked products, further structural characterization could not be carried out. However, results of thermally annealing different combinations of the precursor (PCBCB), PCBM and the BCB compounds and previous studies on these materials in literature 31,32,34,36…”
Section: Synthesis Of Thermal Cross-linkable Fullerenementioning
confidence: 99%
“…These benzocyclobutenes 39 and 40 underwent ring opening isomerisation and cross linking at 100-150 °C, which is about 100 °C lower than the unsubstituted vinylcyclobutene containing polymers (Scheme 6). [26] Synthesis of benzene ring containing more than one annulated cyclobutene ring are not available in the literature except Suzuki's work. [27] Compounds 43 and 44 are of great interest as they can act as precursors to the synthesis of anthracene and higher acene-derived compounds, a valuable building blocks in medicinal chemistry and material science.…”
Section: [2 + 2] Cycloadditionmentioning
confidence: 99%